2021
DOI: 10.3389/fnut.2021.777857
|View full text |Cite|
|
Sign up to set email alerts
|

Estimated Sweetness in US Diet Among Children and Adults Declined From 2001 to 2018: A Serial Cross-Sectional Surveillance Study Using NHANES 2001–2018

Abstract: An agreed-upon measure of total dietary sweetness is lacking hindering assessments of population-level patterns and trends in dietary sweetness. This cross-sectional study used 24-h dietary recall data for 74,461 participants aged ≥ 2 y from nine cycles (2001–2018) of the National Health and Nutrition Examination Survey (NHANES) to evaluate trends in the sweetness of the diet in the United States (US). LCS-containing items were matched to a sugar-sweetened counterpart (e.g., diet cola–regular cola or sucralose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Concern has been expressed about a 'sweetening of the global diet' (3) , although the evidence for this may differ depending on the nature of the analyses and consideration of foods v. beverages. In the USA, sweetness of the diet appears to have declined over the period 2001-2018, driven by reductions in sweeteners in beverages and tabletop sweeteners, with little change in foods (4) . A further analysis concluded that, globally, sweetness and added sugar contents decreased in beverages but increased in packaged foods over the period 2008-2019 (5) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concern has been expressed about a 'sweetening of the global diet' (3) , although the evidence for this may differ depending on the nature of the analyses and consideration of foods v. beverages. In the USA, sweetness of the diet appears to have declined over the period 2001-2018, driven by reductions in sweeteners in beverages and tabletop sweeteners, with little change in foods (4) . A further analysis concluded that, globally, sweetness and added sugar contents decreased in beverages but increased in packaged foods over the period 2008-2019 (5) .…”
mentioning
confidence: 99%
“…beverages. In the USA, sweetness of the diet appears to have declined over the period 2001–2018, driven by reductions in sweeteners in beverages and tabletop sweeteners, with little change in foods (4) . A further analysis concluded that, globally, sweetness and added sugar contents decreased in beverages but increased in packaged foods over the period 2008–2019 (5) .…”
mentioning
confidence: 99%